1982
DOI: 10.1161/01.res.51.3.305
|View full text |Cite
|
Sign up to set email alerts
|

Changes in interstitial volume and masses of albumin and IgG in rabbit skin and skeletal muscle after saline volume loading.

Abstract: SUMMARY. This study was performed on the hindpaws of anesthetized rabbits to determine the effects of acute saline expansion (10% body weight) on the extravascular distribution of water and plasma proteins. Prenodal lymph was collected separately from skin and muscle of the hindlegs. In samples of excised heel skin and gastrocnemius muscle, the extracellular and plasma spaces were measured with 51 Cr EDTA and 125 I albumin, respectively. The albumin and IgG spaces were calculated from measurements of the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
1

Year Published

1984
1984
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 26 publications
(36 reference statements)
3
23
1
Order By: Relevance
“…The increase was approximately the same for all the five EPP. The result does not seem to support an assumption of filtration rate independence and was unexpected because previous studies have shown a reduction in C i /C p of EPP after saline volume loading (25). There are several possible explanations for this aberration.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…The increase was approximately the same for all the five EPP. The result does not seem to support an assumption of filtration rate independence and was unexpected because previous studies have shown a reduction in C i /C p of EPP after saline volume loading (25). There are several possible explanations for this aberration.…”
Section: Discussioncontrasting
confidence: 62%
“…The specific activity for EPP of size 73, 65, 56, and 47 Å was not measured, but based on the results from albumin, we did not anticipate steady state for any of the remaining EPP. In comparison, previous studies measuring lymph concentration of plasma proteins and different-sized dextran achieved stabilization of lymph flow and protein/dextran concentration after 1.5-6 h of measurement (11,25,31,40). Free iodide should not be a source of error in the measurements because the albumin tracer contained Ͻ3% free iodide.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The interstitial space of most tissues is composed of an interlinked matrix of glycosaminoglycans supported by a collagen framework. This matrix forms a gel that restricts plasma proteins from distributing itself in the total intragel volume by either steric or electrostatic exclusion (MULLINS and BELL, 1982). The exclusion of proteins can also contribute to the lowering of protein drainage through lymph but the amount might be smaller.…”
Section: Discussionmentioning
confidence: 99%
“…The dilution of serum by 11 % was also more pronounced than the thoretical 8 % dilution. A shift in the distribution of plasma protein between blood and interstitium (Mullins & Bell, 1982) and/or non-equilibration of infused fluid could explain this discrepancy.…”
Section: Temperaturementioning
confidence: 99%